Association of gamma-glutamyl transferase variability with risk of osteoporotic fractures: A nationwide cohort study. - Dongyeop Kim; Jee Hyun Kim; Heajung Lee; Iksun Hong; Yoonkyung Chang; Tae-Jin Song (PLoS ONE, 2023)
Objectives Gamma-glutamyl transferase (GGT) is related to inflammation, osteoporosis, and vascular diseases. Recently, changes in metabolic parameters have been proposed as osteoporosis biomarkers. We aimed to assess longitudinally the association of GGT variability with osteoporotic fractures. Methods From the National Health Insurance Service-Health Screening Cohort database, participants who underwent three or more health examinations between 2003 and 2008 were included (n = 1,072,432). Variability indexes were as follows: (1) coefficient of variation (CV), (2) standard deviation (SD), and (3) variability independent of the mean (VIM). The primary outcome was occurrence of osteoporotic fracture, defined as identification of one of the following international classification of diseases-10 codes: vertebral fractures (S22.0, S22.1, S32.0, S32.7, T08, M48.4, M48.5, M49.5), hip fractures (S72.0, S72.1), distal radius fractures (S52.5, S52.6), or humerus fractures (S42.2, S42.3). Results During a median of 12.3 years (interquartile range 12.1-12.6), osteoporotic fractures occurred in 49,677 (4.6%) participants. In multivariable analysis, GGT variability based on CV positively correlated with the occurrence of osteoporotic fracture (adjusted hazard ratio [HR] of the highest quartile compared with the lowest quartile 1.15, 95% confidence interval [CI] 1.12-1.18, P < 0.001). These results were consistent even when GGT variability was defined by SD (adjusted HR 1.22, 95% CI 1.19-1.25, P < 0.001) and VIM (adjusted HR 1.12, 95% CI 1.09-1.15, P < 0.001). Conclusions Increased GGT variability is associated with an increased risk of osteoporotic fractures in the Korean population. Maintaining constant and stable GGT level may help reduce the risk of osteoporotic fractures.